Weather and the psychology of purchasing outdoor-movie tickets - Lukas Buchheim; Thomas Kolaska (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
The consequences of many economic decisions only materialize in the future. To make informed choices in such decision problems, consumers need to anticipate the likelihood of future states of the world, the state-dependence of their preferences, and the choice alternatives that may become relevant. This complex task may expose consumers to psychological biases like extrapolative expectations, projection bias, or salience. We test whether customers are affected by such biases when they buy advance tickets for an outdoor movie theater, a real-world situation that, due to the availability of reliable weather forecasts, closely resembles a stylized decision problem under risk. We find that customers' decisions are heavily influenced by the weather at the time of purchase, even though the latter is irrelevant for the experience of visiting the theater in the future. The empirical evidence cannot be fully explained by a range of candidate rational explanations, but is consistent with the presence of the aforementioned psychological mechanisms.
urn:nbn:de:bvb:19-epub-26930-0
Keywords: D03; D12; D81; 330; Projection Bias; Salience; Extrapolative Expectations; Behavioral Economics; Consumer Behavior